Translocator protein deficiency blocks the ferroptosis of malignant peripheral nerve sheath tumors through glutathione peroxidase 4 - Zhang, Xiaoli; Pu, Zhuonan; Ran, Chun; Zhang, Xingnan; Guo, Chao; Deng, Yuxuan; Liu, Jinqiu; Chen, Yingdan; Feng, Jie; Liu, Song (Frontiers in Cellular Neuroscience, 2025)
BackgroundMalignant peripheral nerve sheath tumor (MPNST) is an aggressive soft tissue sarcoma characterized by high recurrence and poor prognosis, necessitating the search for novel therapeutic targets and strategies. This study investigated the expression of mitochondrial translocator protein (TSPO) in MPNST and its role in regulating ferroptosis.MethodsTSPO expression was analyzed in adjacent non-tumor tissues, benign neurofibromas, and malignant tissues using real-time PCR, western blotting, immunohistochemistry staining. Expression levels of classic ferroptosis markers, including AKR1C1 and FTH1 were assessed. Ferroptosis was evaluated by measuring cell viability, ferroptosis marker levels, and intracellular Fe2+ and reactive oxygen species (ROS) levels. Oxidized phospholipid profiles of wild-types and TSPO knockdown MPNST cells were determined using liquid chromatography-mass spectrometry. The potential role of GPX4 in mediating TSPO’s effect on ferroptosis was investigated in vitro.ResultsCompared with adjacent non-tumor tissues and benign neurofibromas, TSPO expression was significantly lower in MPNST specimens. Notably, TSPO expression positively correlated with the classic ferroptosis markers AKR1C1 and FTH1. TSPO-knockdown MPNST cells exhibited significant resistance to ferroptotic cell death. Additionally, biochemical characterization indicated that TSPO deficiency decreased intracellular Fe2+ and ROS. Furthermore, oxidized phospholipids were remarkably reduced in TSPO-knockdown cells. TSPO enriches cellular oxidized phospholipids by downregulating GPX4-GSH antioxidant pathway. Furthermore, GPX4 is elevated in malignant tumors compared to benign specimens and negatively correlated with TSPO expression in clinical tumor specimens.ConclusionOur findings revealed that TSPO deficiency inhibited ferroptosis in MPNST cells by upregulating GPX4 antioxidant pathway, suggesting that mitochondrial TSPO-GPX4-ferroptosis axis may be a promising therapeutic target for improving the outcomes of patients with MPNST.